2019
DOI: 10.1164/rccm.201810-1844le
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Asthma Mortality in the United States: 1999 to 2015

Abstract: In-vitro evaluation of contrast media for assessment of regional perfusion distribution by electrical impedance tomography (EIT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 10 publications
1
27
1
2
Order By: Relevance
“…Asthma is a highly prevalent, chronic, non-communicable disease that affects up to 4.4% of the world’s population ( http://www.globalasthmareport.org ; https://www.who.int/news-room/q-a-detail/asthma ). Its recurrent nature leads to frequent hospitalizations and high mortality, ranging from 2 to 4/100,000 [ 13 ]. Respiratory viruses can trigger asthma exacerbations, which can increase the severity of the infectious condition [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a highly prevalent, chronic, non-communicable disease that affects up to 4.4% of the world’s population ( http://www.globalasthmareport.org ; https://www.who.int/news-room/q-a-detail/asthma ). Its recurrent nature leads to frequent hospitalizations and high mortality, ranging from 2 to 4/100,000 [ 13 ]. Respiratory viruses can trigger asthma exacerbations, which can increase the severity of the infectious condition [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of mortality trend in age groups 5 to 9 or 10 to 14 years is consistent with the findings of a recent multi country study that found no significant changes in mortality from 2006 to 2012 34 in the group that included a combination of asthmatic children and adults (age 5‐34 years). The recent US study 14 from 1999 to 2015 did not show changes in asthma mortality either with low mortality rates in children aged 1 to 14.…”
Section: Discussionmentioning
confidence: 83%
“…Some of these studies, including an old Mexican study, 13 reported a favorable decreasing trend of asthma mortality overtime. Contrary to this, a recent US study found no significant changes from 1999 to 2015 and low mortality rate in children aged 1 to 14 14 . However, analysis by zone of residence was not performed neither the Mexican nor US studies.…”
Section: Introductionmentioning
confidence: 76%
“…Asthma is a highly prevalent, chronic, non-communicable disease that affects up to 4.4% of the world's population (http://www.globalasthmareport.org; https://www.who.int/news-room/q-a-detail/asthma). Its recurrent nature leads to frequent hospitalizations and high mortality, ranging from 2 to 4/100,000 (13).…”
Section: Discussionmentioning
confidence: 99%